Red ginseng polysaccharide promotes ferroptosis in gastric cancer cells by inhibiting PI3K/Akt pathway through down-regulation of AQP3 - Yan Wang; Wen-Xian Guan; Yuan Zhou; Xiao-Yu Zhang; Hai-Jian Zhao (Cancer Biology & Therapy)
Objective This study aims to investigate the effect of red ginseng polysaccharide (RGP) on gastric cancer (GC) development and explore its mechanism.Methods GC cell lines AGS were treated with varying concentrations of RGP (50, 100, and 200 μg/mL). AGS cells treated with 200 μg/mL RGP were transfected with aquaporin 3 (AQP3) overexpression vector. Cell proliferation, viability, and apoptosis were evaluated by MTT, colony formation assay, and flow cytometry, respectively. Real-time quantitative reverse transcription PCR (qRT-PCR) was used to detect the expression of AQP3. The levels of Fe2+, malondialdehyde, and lactate dehydrogenase were measured using their respective detection kits, and the reactive oxygen species levels was determined by probe 2’,7’-dichlorodihydrofluorescein diacetate. The expression of ferroptosis-related protein and PI3K/Akt pathway-related protein were assessed by western blot. In vivo experiments in nude mice were performed and the mice were divided into four groups (n = 5/group) which gavage administrated with 150 mg/kg normal saline, and 75, 150, 300 mg/kg RGP, respectively. Their tumor weight and volume were recorded.Results RGP treatment effectively inhibited the proliferation and viability of AGS cells in a dosage-dependent manner and induced apoptosis. It induced ferroptosis in AGS cells, as well as inhibiting the expression of PI3K/Akt-related proteins. AQP3 overexpression could reversed the effect of RGP treatment on ferroptosis. Confirmatory in vivo experiments showed that RGP could reduce the growth of implanted tumor, with increased RGP concentration resulting in greater tumor inhibitory effects.Conclusion RGP might have therapeutic potential against GC, effectively inhibiting the proliferation and viability of AGS cells.